The effects of Surfactin on sprayed droplets in flat fan, full cone, and low energy precision application bubbler nozzles: droplet formation and spray breakup - Stallbaumer-Cyr, Emily M.; Aguilar, Jonathan; Betz, Amy R.; Derby, Melanie M. (Frontiers in Mechanical Engineering, 2024)
Agriculture is the largest user of water globally (i.e., 70% of freshwater use) and within the United States (i.e., 42% of freshwater use); irrigation ensures crops receive adequate water, thereby increasing crop yields. Surfactants have been used in various agricultural spray products to increase spray stability and alter droplet sizes. The effects of the addition of surfactant (0.1 wt% Surfactin; surface tension of 29.2 mN/m) to distilled water (72.79 mN/m) on spray dynamics and droplet formation were investigated in four flat fan (206.8 -413.7 kPa), one full cone (137.9 -413.7 kPa), and three LEPA bubbler (41.4 kPa -103.4 kPa) nozzles. The flat fan and cone nozzles experienced second windinduced breakup (i.e., unstable wavelengths drive breakup) of the liquid sheets exiting the nozzle; the addition of surfactant resulted in an increased breakup length and a decreased droplet size. The fan nozzles volumetric median droplet diameter decreased with the addition of surfactant (e.g., decreased by 26.3 -65.6 µm in one nozzle). The full cone nozzle volumetric median droplet diameter decreased initially with the addition of surfactant (27.8 µm, 14.3 µm, and 13.4 µm at 137.9, 206.8, and 310.3 kPa respectively), but increased at 413.7 kPa (24.3 µm). Sprays from the bubbler nozzles were measured and observed to experience Rayleigh (i.e., the droplets form via capillary pinching at the end of the jet) and first wind-induced breakup (i.e., air impacts breakup along with capillary pinching). The effect of Surfactin on droplet size was minimal for the 41.4 kPa bubbler nozzle. The addition of surfactant increased the diameter of the jet or ligament formed from the bubbler plate, thereby increasing the breakup length and the droplet size at 68.9 and 103.4 kPa (droplet size increased by 750.6 µm and 4462.7 µm, respectively).